If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + -1b) = 0 (a * 2 + -1b * 2) = 0 (2a + -2b) = 0 Solving 2a + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 2a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 2a + 0 = 0 + 2b 2a = 0 + 2b Remove the zero: 2a = 2b Divide each side by '2'. a = b Simplifying a = b
| 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 | | 4p-17.0=53.00 | | 0.1x=0.35 | | 9x-2y/3*5z | | 0.35x=0.1 | | -8y-10xy= | | 0.1x-0.01x=1 | | -5b-b= | | -2x^2+3x^2= | | -2x^2-3x^2= | | 3x/5-0.5=109 |